Hydrogen gas sensor based on metal oxide nanoparticles decorated graphene transistor1. Issue 22 (14th June 2015) - Zhang, Zhangyuan; Zou, Xuming; Xu, Lei; Liao, Lei; Liu, Wei; Ho, Johnny; Xiao, Xiangheng; Jiang, Changzhong; Li, Jinchai
<x xml:space="preserve">Abstract</x> With the high mobility of graphene and good sensitivity of metal oxide NPs, our gas sensors show fast response (∼1 s) and high sensitivity at relatively low temperature.